2014
DOI: 10.1111/sms.12333
|View full text |Cite
|
Sign up to set email alerts
|

Tendon overload results in alterations in cell shape and increased markers of inflammation and matrix degradation

Abstract: Tendon injury is thought to involve both damage accumulation within the matrix and an accompanying cell response. While several studies have characterized cell and matrix response in chronically injured tendons, few have assessed the initial response of tendon to overloadinduced damage. In this study, we assessed cell response to cyclic loading. Fascicle bundles from the equine superficial digital flexor tendon were exposed to cyclic loading in vitro, designed to mimic a bout of high-intensity exercise. Change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 51 publications
(72 reference statements)
10
75
0
Order By: Relevance
“…Tenocytes have also been shown to possess TNFα and IL-21 signalling systems,30 31 notably, with IL-21 production being demonstrated to increase in response to the application of TNFα and IL-1β. The dynamic response of tendon cells and tendon to mechanical load appears related to an extremely intricate interplay between inflammatory mediators, matrix enzymes and the matrix itself;27 32 certainly evidence has shown that tendon's reactive response to load has an inflammatory component. The concept of the inflammatory component's importance is reinforced by the findings in animal models of tendinopathy which have demonstrated that inflammatory cells accumulate,33–35 and that inflammatory cytokines increase 25 36–38.…”
Section: Discussionmentioning
confidence: 99%
“…Tenocytes have also been shown to possess TNFα and IL-21 signalling systems,30 31 notably, with IL-21 production being demonstrated to increase in response to the application of TNFα and IL-1β. The dynamic response of tendon cells and tendon to mechanical load appears related to an extremely intricate interplay between inflammatory mediators, matrix enzymes and the matrix itself;27 32 certainly evidence has shown that tendon's reactive response to load has an inflammatory component. The concept of the inflammatory component's importance is reinforced by the findings in animal models of tendinopathy which have demonstrated that inflammatory cells accumulate,33–35 and that inflammatory cytokines increase 25 36–38.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that these processes can be adaptive, and whilst the speed of adaptation is slow, tendon can thicken and strengthen in response to use 53; 54 . However, both overuse and underuse have been reported to initiate a more rapid catabolic cell response and tendon degeneration 38; 55; 56; 57 .…”
Section: Biological Functionmentioning
confidence: 99%
“…For example, recent data has begun to quantify the development of matrix disruption with tendon overuse, correlating this to reduced tendon mechanics 79 . Early overuse damage has been identified within the non-collagenous regions of tendon, and overuse shown to initiate an immediate inflammatory response in tendon 38 , alongside an upregulation of matrix degradation and cell apoptosis 80 . However, whilst these data provide important insights into tendinopathy, we still lack a functionally ideal model to enhance further studies.…”
Section: Tendinopathymentioning
confidence: 99%
“…The aim of this study was to examine the metabolic response of normal and tendinopathic tendons to ESWT treatment and provide the first in vivo evidence of the biological mechanisms underpinning ESWT treatment outcomes. Specifically, we investigated the acute response of inflammatory cytokines associated with mechanical loading, repair processes and tenocyte health (John et al, 2010;Thorpe et al, 2015), and also matrix metalloproteases (MMPs), which are implicated in the homeostasis of tissue regeneration Riley et al, 2002), for the purpose of improving our understanding of the mechanisms underlying observed effects.…”
Section: Introductionmentioning
confidence: 99%